Teachers with a refugee background work as educators in Germany - Özdemir, Yusuf; Polat, Seyat (Intelektual Pustaka Media Utama, 2024)
This study's focus is to determine refugee teachers' views regarding their ability to work as teachers in Germany, their initiatives, and the challenges they face. In this context, the study was conducted based on qualitative research methodology. In order to collect data a total of 265 teachers residing in the 16 states of Germany were reached. Upon examining the results, it is observed that the majority of participants express a desire to work as teachers in Germany, while only a few have actually obtained the opportunity to work as teachers in Germany. More than half of the participants who are currently working as teachers reside in the North Rhine-Westphalia state. When analyzing the results, it becomes evident that a significant portion of the participants are strongly inclined to pursue a teaching career in Germany. However, the data reveals that the actual attainment of employment as teacher in Germany remains relatively low among the respondents. Furthermore, it is noteworthy that a majority of the teachers currently employed in the profession are concentrated in the North Rhine-Westphalia state.